Closing the data gap: equality, human rights, and the challenge of BAME representation in UK policing - Yusuf, Hakeem O. (Human rights review, 2025)
The recruitment and retention of individuals from Black and Minority Ethnic (BAME) communities within UK police forces is not only a persistent operational challenge, but also a critical human rights issue. This paper examines the failure of UK police forces to maintain accessible, comprehensive records on BAME recruitment and retention—a deficiency that undermines both domestic legal duties and international human rights obligations. By integrating empirical data obtained through Freedom of Information (FOI) requests with a doctrinal analysis of the Equality Act 2010 and the International Convention on the Elimination of All Forms of Racial Discrimination (ICERD), this study argues that the ‘data gap’ constitutes a breach of the Public Sector Equality Duty (PSED) and imperils the pursuit of substantive equality in policing. This research contributes to the existing literature on institutional accountability and state data practices by advancing a framework that links data transparency with the broader imperatives of human rights protection.